Human rights and national literature: a comparative study of the experiences in Malaysia, Thailand and the Philippines - Abdul Manaf, Nor Faridah (IIUM Press,International Islamic University Malaysia, 2008)
This paper studies the experience encountered by three South Asian nations in the face of globalisation in which nationalism is often seen as something negative and regressive. The paper analyses how these three nations strengthen the position of national literature in the face of globalisation. It also compares how minority voices attract international attention and expose themselves to two risks. One of the risks is being dominant over national literature which will likely create tension within the nation. The second risk is of being marginalised and losing their iterary importance in their own land.